2014
DOI: 10.1088/0953-8984/26/14/145501
|View full text |Cite
|
Sign up to set email alerts
|

Fermi level density of states modulation without charge transfer in nickelate superlattices

Abstract: Abstract. By using first-principles density functional theory calculations for (LaNiO 3 ) m /(SrTiO 3 ) n superlattices, we report a systematic way of electronic response to the interface geometry. It is found that Fermi level density of states of metallic nickelate layers is significantly reduced without charge transfer in the vicinity of interface to the insulating SrTiO 3 . This type of electronic state redistribution is clearly distinctive from other interface phenomena such as charge and orbital reconstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The predominant Ni d 8 electronic configuration is likely to arise primarily from charge transfer effects, as unlike some other perovskites, the 3d levels in LaTiO 3 lie near to the Fermi level of LaNiO 3 -heterostructures [60,61]. Ti L-edge XAS showed that the Ti charge state changes from 3+ to close to 4+ upon heterostructuring indicating that a large fraction of the one electron per Ti has been transferred to other layers in the heterostruc- ture [17] driving Ni towards a d 8 state.…”
mentioning
confidence: 99%
“…The predominant Ni d 8 electronic configuration is likely to arise primarily from charge transfer effects, as unlike some other perovskites, the 3d levels in LaTiO 3 lie near to the Fermi level of LaNiO 3 -heterostructures [60,61]. Ti L-edge XAS showed that the Ti charge state changes from 3+ to close to 4+ upon heterostructuring indicating that a large fraction of the one electron per Ti has been transferred to other layers in the heterostruc- ture [17] driving Ni towards a d 8 state.…”
mentioning
confidence: 99%
“…8 Electrical transport measurements showed an enhanced sheet conductivity for LNO/SrTiO 3 (001) SLs on (LaAlO 3 ) 0.3 (Sr 2 AlTaO 6 ) 0.7 (LSAT), 13,14 whereas standing-wave excited photoemission experiments and ab initio calculations reported a reduction of the electronic density of states (DOS) at the Fermi energy on LSAT and SrTiO 3 (STO). [15][16][17] The LNO/STO(001) SLs bear two major differences to commonly studied oxide interfaces. Unlike the nonpolar LNO/LAO(001) SLs, in LNO/STO(001) SLs there is a charge discontinuity at the interface depending on the layer stacking that can lead to either n-type [(LaO) + /(TiO 2 ) 0 ] or p-type [(NiO 2 ) − /(SrO) 0 ] δ-doping.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has recently been reported that LaNiO 3 , which is a paramagnetic metal in the bulk phase, shows insulating behavior with magnetic order in a superlattice 21,22 . There have been a number of subsequent studies about nickelate heterostructures [22][23][24][25][26][27][28][29][30][31][32][33] , which show a potential for rich physics, but there has not been systematic studies about the effect of doping in these systems yet.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we examine the effect of doping on the nickelate superlattice by taking (LaNiO 3 ) 1 /(SrTiO 3 ) 1 as a prototype example [31][32][33][34] . We employed first-principles density functional theory (DFT) calculations augmented with mean-field treatment of on-site Coulomb interaction, the so-called DFT+U methodology, to consider the role of electron correlations inherent in the Ni e g orbitals.…”
Section: Introductionmentioning
confidence: 99%